Faktor- Faktor Yang Mempengaruhi Kinerja Pegawai Puskesmas Talang Kelapa Kabupaten Banyuasin Tahun 2017 - Herman, Sofa (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat (IAKMI) Provinsi Sumatera Selatan, 2018)
Health development is organized to increase awareness, willingness, and healthy living ability for everyone to realize the highest level of public health. The high disparities and the need to accelerate the increased accessibility of health services require adequate resources support and appropriate health policy and development strategies. The purpose of this research is to analyze the factors that influence the performance of the employees at Talang Kelapa Public Health Center, Talang Kelapa Village, Talang Kelapa Subdistrict, Banyuasin Regency. This research is a quantitative research with Cross Sectional design. The sample of this research is 38 civil servants in Talang Kelapa Public Health Center. The result of bivariate with chi-square test shows that there is correlation between employee's ability to performance of Puskemas employee (P Value = 0.002), there is correlation between employee's motivation to Puskesmas employee performance (P Value = 0.005) P Value = 0.034). The results of ultivariate with multiple logistic regression test showed that the motivation and employee opportunity were simultaneously related to the performance of Talang Kelapa Community Health Center staff. Talang Kelapa Kab. Banyuasin Year 2017 (P Value = 0.000). From this research is expected to employees of Puskesmas Talang Kelapa Kab. Banyuasin can improve work skills, work motivation and job opportunities to improve better performance.